2014
DOI: 10.1016/j.placenta.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal prenatal smoking and alcohol consumption on the placenta-to-birth weight ratio

Abstract: Background Maternal influence on fetal growth is mediated through the placenta and this influence may have an implication for the offspring’s long-term health. The placenta-to-birth weight ratio has been regarded as an indicator of placental function. However, few studies have examined the effect of maternal lifestyle exposures on the placenta-to-birth weight ratio. This study aims to examine the associations of maternal prenatal smoking and alcohol consumption with the placenta-to-birth weight ratio. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 32 publications
(34 reference statements)
1
26
0
3
Order By: Relevance
“…Nicotine and amphetamine use have both been associated with placental vasoconstriction and an increased risk of associated outcomes, including placental hemorrhage and abruption, premature delivery, and fetal growth restriction thought to be due to decreased placental blood flow. In the large Australian study noted above (Wang et al., ), maternal cigarette smoking was associated with both decreased placental weight and increased placenta‐to‐birthweight ratio. Using a large, de‐identified, state‐based medical record database, Mbah and colleagues () compared the prevalence of PAS among 5,026 women whose delivery discharge records listed an ICD‐9 code identifying cocaine abuse to 5,026 women without cocaine‐associated ICD‐9 codes, adjusting for propensity scores comprised of potential demographic confounders and binary (yes/no) tobacco and alcohol abuse variables.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Nicotine and amphetamine use have both been associated with placental vasoconstriction and an increased risk of associated outcomes, including placental hemorrhage and abruption, premature delivery, and fetal growth restriction thought to be due to decreased placental blood flow. In the large Australian study noted above (Wang et al., ), maternal cigarette smoking was associated with both decreased placental weight and increased placenta‐to‐birthweight ratio. Using a large, de‐identified, state‐based medical record database, Mbah and colleagues () compared the prevalence of PAS among 5,026 women whose delivery discharge records listed an ICD‐9 code identifying cocaine abuse to 5,026 women without cocaine‐associated ICD‐9 codes, adjusting for propensity scores comprised of potential demographic confounders and binary (yes/no) tobacco and alcohol abuse variables.…”
mentioning
confidence: 86%
“…In other disease models, reduced placental size has been associated with growth restriction in the child, a hallmark feature of FASD. In a recent, large Australian population‐based study examining risk factors for sudden infant death syndrome, mothers who reported any alcohol consumption during pregnancy had a lower average placenta‐to‐birthweight ratio than alcohol abstainers after controlling for maternal cigarette smoking and potential confounders, but no effects were seen on placental weight per se (Wang et al., ). The lack of effect on placental weight may have been due to low maternal drinking levels and/or confounding with other exposures, since data regarding frequency or amount of alcohol consumed were not available, and maternal drug use was not assessed.…”
mentioning
confidence: 99%
“…A study focused on placental pathological changes in smoking pregnant women, revealed that cigarette use was not associated with chorioamnionitis, villitis, or deciduitis (Carter et al, 2016). On the contrary, another study evidenced that maternal smoking during pregnancy was associated with lower placental and birth weight, and with a higher placenta-to-birth weight ratio, when compared with non-smoking mothers (Wang et al, 2014). Regarding the molecular pathways whereby maternal smoking during pregnancy may affect proper fetal growth and development, recently many researchers have shown that they are epigenetic in nature, being mainly represented by changes in DNA methylation and in microRNA expression in fetuses exposed to maternal smoke (Knopic et al, 2012).…”
Section: Maternal Dietmentioning
confidence: 99%
“…Within this tug-of-war [57], the influence of maternal phenotype on fetal growth is well established. For example, reduced rates of fetal growth are typical of first-borns, owing to incomplete penetration of the spiral arteries [100] of the offspring of mothers who smoke or are anemic [101,102] and of the offspring of mothers with lower body mass index [103,104]. The tug-of-war brings the offspring into contact with a composite maternal phenotype.…”
Section: Integrating Ecological Signalsmentioning
confidence: 99%